Queer anatomies : aesthetics and desire in the anatomical image, 1700-1900 - Sappol, Michael (2024)
"Anatomical drawing has long occupied a unique space between science and art - precise and informative but often also strangely aesthetically pleasing. Filled with images of dead and dissected bodies and body-parts, it was often by turns monstrous, provocative, playful and theatrical. Queer Anatomies reveals and explores the possibilities of sexual desire within anatomical drawings of the 18th and 19th centuries. It uncovers the subtle eroticism of certain anatomical illustrations, and the queerness of the men who made, used and collected them. A foundational subject in both the art academy and medical school, anatomy was a privileged, male-heavy domain in which dissected naked bodies, genitalia, and the rectum were available for representation. In the Victorian era, when same-sex desire and the human sexual apparatus were debarred from polite conversation and printed discourse, even seemingly sober illustrations could be charged with erotic, often homoerotic, undertones. Offering essayistic reflection and close readings of key images and texts - including works by Gautier d'Agoty, William Cheselden, Joseph Maclise and many others - Queer Anatomies places medical history, connoisseurship, queer studies, and art history into dialog with each other, and sheds new light on the history of anatomical illustration and the body. The book contains full-colour reproductions of a range of drawings - from renderings of dead and dissected bodies, penises, vaginas, rectums, hands, and skin, to images of male viewers gazing upon drawings, paintings, prints and sculptures of the naked body. Some are brilliant, accurate representations of the body, others are barely competent. But all are full of interest and offer a fascinating insight into the subversive reception of the naked body in the buttoned-up Victorian era"--
Theory -- Objects -- Gagutier -- Cheselden -- Between men -- Prologue: Nicolas-Henri Jacob -- Joseph Maclise.
Includes bibliographical references (pages [233]-249) and index.
Keywords: Anatomy, Artistic; Sex (Biology) in art; Sex (Psychology) in art; Homosexuality and art